PENGARUH GREENWASHING DAN SUSTAINABILITY ASSURANCE TERHADAP KINERJA KEUANGAN - Taufik Bin Abad; Inon Listyorini (Paulus Journal of Accounting (PJA), 2025)
This study investigates the impact of greenwashing and sustainability assurance practices on financial performance in companies listed on ASEAN Stock Exchange. The theoretical framework employed are agency theory and signalling theory. The research sample comprises firms operating in sectors with high potential for environmental impact, including basic materials, consumer cyclicals, consumer non-cyclicals, energy, industrials, and technology. Data were obtained from Revinitif, sustainability reports, and corporate financial statements for the 2022–2023 period. The empirical findings reveal that greenwashing practices have a significant negative effect on financial performance at the 1% significance level. In contrast, sustainability assurance has not influence on financial performance. This study contributes to the literature by offering empirical evidence on the effects of greenwashing and sustainability assurance in the context of emerging capital markets.